Analisis Implementasi Green Intellectual Capital Terhadap Sustainable Development pada Perusahaan Energi di Negara ASEAN (Lembaga Pengembangan Kinerja Dosen, 2025)
This study investigates the impact of Green Intellectual Capital (GIC)—consisting of Green Human Capital (GHC), Green Structural Capital (GSC), and Green Relational Capital (GRC)—on Sustainable Development (SD) within energy companies operating across the ASEAN region. The research is motivated by the increasing demand for sustainable business practices in response to global environmental challenges, particularly in sectors with significant environmental footprints such as energy. Employing a quantitative approach, the study uses secondary data obtained from 45 publicly listed energy companies in Indonesia, Malaysia, Thailand, and the Philippines for the period 2022–2023. The data were analyzed using multiple linear regression to assess both the collective and individual effects of GIC components on sustainable development outcomes. The findings demonstrate that, taken together, the three dimensions of GIC significantly influence sustainable development. However, when examined individually, only Green Human Capital and the control variable—firm size—show a statistically significant positive effect. Green Structural Capital and Green Relational Capital, while positively associated, do not exhibit significant impacts. These results underline the strategic importance of human-centric capabilities in driving sustainability initiatives, particularly in sectors where operational activities are closely linked to environmental concerns. The study contributes to the existing literature by emphasizing the role of intangible assets in achieving corporate sustainability. It also provides practical implications for managers and policymakers to prioritize capacity building, workforce development, and organizational culture that supports green innovation. Future research is recommended to adopt longitudinal and multi-method approaches to explore causality and deepen the understanding of GIC in various industrial contexts.